First report of cutaneous lepidopterism by Hylesia invidiosa (Lepidoptera: Saturniidae): outbreak description and review of the literature - Chaves González, Luis Enrique (2026)
Esta corresponde a una versión PREPRINT del manuscrito aceptado (al 12 de marzo, 2026) para publicación en el American Journal of Tropical Medicine and Hygiene.